2023
DOI: 10.3389/fpubh.2022.1073809
|View full text |Cite
|
Sign up to set email alerts
|

Role of hospitals in recovery from COVID-19: Reflections from hospital managers and frontliners in the Eastern Mediterranean Region on strengthening hospital resilience

Abstract: BackgroundCOVID-19 highlighted the critical role that hospitals play throughout the prolonged response and continuous recovery stages of the pandemic. Yet, there is limited evidence related to hospitals in the recovery stage, particularly capturing the perspectives of hospital managers and frontliners in resource-restrained and humanitarian settings.ObjectiveThis paper aims to capture the perspectives of hospital managers and frontliners across the Eastern Mediterranean Region on (1) the role of hospitals in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Based on the Italian qualitative study, education emerged as the most prominent theme. The health managers believed they had an internal-facing obligation to train their staff (20). The results of a Chinese qualitative study showed that educational videos were a source of support in the COVID-19 pandemic because they had worked in non-infectious departments previously (21).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Italian qualitative study, education emerged as the most prominent theme. The health managers believed they had an internal-facing obligation to train their staff (20). The results of a Chinese qualitative study showed that educational videos were a source of support in the COVID-19 pandemic because they had worked in non-infectious departments previously (21).…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals, as a crucial component of the healthcare system, play a vital role in epidemic response and serve as the primary point of contact for communities during emergencies. Therefore, ensuring the stability and resilience of hospitals in the face of major infectious diseases is essential ( 4 ). Scholars have proposed the concept framework of hospital resilience for disaster response, which includes hospital safety, disaster preparedness and resources, continuous basic medical services, and recovery and adaptation as the four key elements ( 5 ).…”
Section: Introductionmentioning
confidence: 99%